In Vitro α-Amylase and Protein Glycation Inhibitory Activity of the Aqueous Extract of Flueggea leucopyrus Willd - Vishmi Sachindra Thrikawala; Srianthie A. Deraniyagala; Chamira Dilanka Fernando; Dinusha Nishani Udukala (Journal of Chemistry)
There is much interest in plant-based medicine with antidiabetic and antiglycation properties. Chronic hyperglycemia plays a vital role in the development of long-term diabetic complications by inducing protein glycation and the gradual formation of advanced glycation end products (AGEs) in various body tissues. The main objectives of this study were to investigate the aqueous extract of the whole plant of Flueggea leucopyrus Willd (FLAE), a medicinal plant used in traditional medicine in Sri Lanka for its in vitro α-amylase inhibitory activity and its inhibitory potential on the formation of AGEs. α-Amylase inhibitory activity determined by 3,5-dinitrosalicylic acid method revealed that FLAE possesses 29%–91% inhibitory activity at a concentration range of 2.5–400 μg/mL, respectively. Nonenzymatic protein glycation inhibitory capacity assessed by bovine serum albumin-fructose fluorescence spectrometric assay showed that FLAE at 15.6–250.0 μg/mL inhibited AGE formation by 0.9%–98%, respectively. Radical scavenging ability of FLAE using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and total phenolic and flavonoid contents of FLAE were also determined. This study shows that Flueggea leucopyrus Willd not only inhibits α-amylase enzyme, which is known to break starch to glucose, but also inhibits the formation of AGEs, which occur due to chronic hyperglycemia that leads to the onset of diabetic complications.